Environmental and Behavioral Factors Analysis of Malaria Incidents - Dewi Agustina; Putra Apriadi Siregar (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2021)
The emergence of malaria is inseparable from the anopheles mosquito that can survive the existing environment. Community behaviour also plays an important role in the risk of getting mosquito bites. Indonesia still has malaria-endemic districts/cities. This objective is to determine the effect of environmental and behavioural factors on malaria incidence. This study used a cross-sectional design; the population in this study were all people who visited the malaria post in the Percut Village, Deliserdang Regency, totalling 140 people. The data will be analyzed using multiple logistic regression tests. The logistic regression test results showed that the habit of leaving the house (p-value = 0.007), the use of mosquito nets (p = 0.001), affected the incidence of malaria in the village of Percut, Deliserdang Regency. The most dominant variable in malaria incidence was the use of bed nets with an exp B value of 11.68.